Glyphosate: Too Much of a Good Thing? - Cuhra, Marek; Bøhn, Thomas; Cuhra, Petr (Frontiers in Environmental Science, 2016)
Although previously accepted as the less toxic alternative, with low impact on animals, farmers as well as consumers who are exposed to residues in food, glyphosate chemicals are now increasingly controversial as new evidence from research is emerging. We argue that specific aspects of the history, chemistry and safety of glyphosate and glyphosate-based herbicides should be thoroughly considered in present and future re-evaluations of these dominant agrochemicals: · Glyphosate is not a single chemical, it is a family of compounds with different chemical, physical and toxicological properties. · Glyphosate is increasingly recognized as having more profound toxicological effects than assumed from previous assessments. · Global use of glyphosate is continuously increasing and residues are detected in food, feed and drinking water. Thus, consumers are increasingly exposed to higher levels of glyphosate residues, and from an increasing number of sources. · Glyphosate regulation is predominantly still based on primary safety-assessment testing in various indicator organisms. However, archive studies indicate fraud and misbehavior committed by the commercial laboratories providing such research. We see emerging evidences from studies in test-animals, ecosystems indicators and studies in human health, which justify stricter regulatory measures. This implies revising glyphosate residue definitions and lowering Maximum Residue Limits (MRLs) permissible in biological material intended for food and feed, as well as strengthening environmental criteria such as accepted residue concentrations in surface waters. It seems that although recent research indicates that glyphosates are less harmless than previously assumed and have complex toxicological potential, still regulatory authorities accept industry demands for approving higher levels of these residues in food and feed.